REGULATION ON PERSONAL DATA PROTECTION IN THE USE OF E-COMMERCE SERVICES - Kurniasandi, Domi Dwi; Aprilia, Sherly Nanda; Indradjaja, Nobella; Chamdani, Chamdani (EQUALEGUM International Law Journal, 2024)
Background. To realize legal certainty in business, the State protects consumer rights. Consumer rights become a proper subject of research due to the rapid technological advancement impacting the use of electronic devices, which also become a place of business transactions through e-commerce. To be able to use marketplace services, service users must fill out personal data and verify it. The data will be saved in the Big Data by the e-commerce service provider, and there is a potential for data misuse and leak as how they more frequently occur nowadays. This research aims to observe consumer personal data protection in Indonesia. Research Method. The normative legal method reviews several laws and regulations. Findings. There have been various regulations related to personal data protection, specifically Law No. 27 of 2022 regarding Personal Data Protection. However, several issues remain that become a basis for the researchers' suggestions. Conclusion. The Consumer Protection Law states that consumers have the right to safety and security in consuming goods and/or services but does not specifically regulate consumer data protection.